A Webcast of Bird Nesting as a State-of-the-Art Citizen Science - Zárybnická, Markéta; Sklenicka, Petr; Tryjanowski, Piotr (PLoS biology, 2017)
The quality of people's knowledge of nature has always had a significant influence on their approach to wildlife and nature conservation. However, direct interactions of people with nature are greatly limited nowadays, especially because of urbanization and modern lifestyles. As a result, our isolation from the natural world has been growing. Here, we present an example of a state-of-the-art Citizen Science project with its educational, scientific, and popularizing benefits. We conclude that modern media and new forms of education offer an effective opportunity for inspiring children and others to have fun learning to act like scientists. This approach provides broad opportunities for developing the hitherto neglected educational potential of Citizen Science.
Keywords: Webcasts as Topic; Research; věda; ptáci; Birds; Animals; Science; lidé; webová vysílání jako téma; Humans; hnízdění; zvířata; výzkum; Nesting Behavior